Public Health and Social Medicine - KUMBAN WALTER CHUCK (The Graduate School, Ajou University, 2024)
Cancer has been a leading cause of death in recent times due to numerous factors, including genetic factors, physical factors, lifestyles, hormone secretions, infections, and radiation which has necessitated the implementation of cancer screening programs. Recently there has been much controversy regarding the adherence to cancer screening services among people with chronic conditions including diabetes and hypertension. People with chronic conditions may be less likely to take part in cancer preventive procedures because of competing needs for chronic disease management and also due to the fact that some chronic conditions, are directly or indirectly associated with cancer mortality and morbidity. There is a need to understand the importance of sufficient use of cancer preventive services, including cancer screening in these populations, and to improve the effectiveness of cancer screening programs. This study is aimed at assessing cancer screening uptake among Koreans with chronic conditions including diabetes and hypertension. The data from 8,111 participants of the 2019 Korea National Health and Nutrition Examination Survey (KNHANES). The final sample data of 5,362 participants was eligible for the study. This study included cancer-free men and women of various age groups in major cancers as stipulated by the Korean Cancer National Screening Program. Cancer screening rates were compared among participants with diabetes and hypertension. Hypertension included a complete measurement of diastolic and systolic blood pressure, while diabetes was defined based on diabetes status diagnosed by a physician, fasting blood glucose of ≥126mg/dl or those who received treatment using insulin. Baseline characteristics and cancer screening rates were calculated using weighted frequencies and multivariate logistic regression models at a 95% confidence interval. STATA version 12.0 was used for data analysis with P<0.05 considered significant. Participants with diabetes, hypertension, and those with hypertension and diabetes as chronic conditions had significantly reduced cancer screening rates [(OR)=0.72, 95%CI=(0.60-0.84), P-value < 0.001], [(OR)=0.58, 95%CI=(0.43-0.79), P-value<0.001], [(OR)=0.68, 95%CI=(0.58-0.80), P-value < 0.001] respectively compared to those without these conditions. Participants with diabetes and hypertension showed reduced cancer screening rates. Even though much research is needed to explore the mechanism behind reduced cancer screening rates in participants with chronic conditions, including diabetes and hypertension, previous research has highlighted that these low screening rates may be attributed to patients with chronic diseases’ reluctant attitudes toward healthcare services as they underestimate the comparative advantages of screening services. This research highlighted that the Korean cancer screening programs may need to consider additional pathways to reduce the interruption of cancer screening procedures and also to improve the cancer screening rates in people with chronic conditions to reduce future complications and increase mortality. Keywords: Diabetes, hypertension, cancer, screening, Korea|암은 유전적 요인, 신체적 요인, 생활습관, 호르몬 분비, 감염, 방사선 등 다양한 요인으로 인해 최근 사망 원인의 1위를 차지하고 있으며, 이로 인해 암 검진 프로그램 시행이 필요해졌습니다. 최근 당뇨병, 고혈압 등 만성질환자의 암검진 순응도에 대해 많은 논란이 일고 있다. 만성 질환을 앓고 있는 사람들은 만성 질환 관리에 대한 경쟁적인 요구와 일부 만성 질환이 암 사망률 및 질병률과 직간접적으로 연관되어 있다는 사실로 인해 암 예방 절차에 참여할 가능성이 낮을 수 있습니다. 이들 인구 집단에서 암 검진을 포함한 암 예방 서비스의 충분한 이용의 중요성을 이해하고 암 검진 프로그램의 효율성을 향상시킬 필요가 있습니다. 이번 연구는 당뇨병, 고혈압 등 만성질환을 앓고 있는 한국인의 암 검진 활용도를 평가하는 것을 목표로 한다._x000D_ 2019년 국민건강영양조사(KNHANES) 참가자 8,111명의 데이터입니다. 5,362명의 참가자의 최종 샘플 데이터가 연구에 적합했습니다. 본 연구에는 한국암국가검진 프로그램에서 규정한 주요 암의 다양한 연령층의 암이 없는 남성과 여성이 포함되었습니다. 당뇨병과 고혈압 참가자의 암 검진율을 비교했습니다. 고혈압은 이완기혈압과 수축기혈압을 모두 측정한 것을 의미하며, 당뇨병은 의사가 진단한 당뇨병 상태, 공복 혈당이 126mg/dl 이상 또는 인슐린 치료를 받은 사람을 기준으로 정의되었습니다. 기준 특성 암 검진율은 95% 신뢰 구간에서 가중 빈도와 다변량 로지스틱 회귀 모델을 사용하여 계산되었습니다. STATA 버전 12.0은 P<0.05가 유의미한 것으로 간주되는 데이터 분석에 사용되었습니다._x000D_ 당뇨병, 고혈압, 만성질환인 고혈압, 당뇨병이 있는 참가자는 암 검진율이 유의하게 감소했습니다 [(OR)=0.72, 95%CI=(0.60-0.84), P-value < 0.001], [(OR)= 이러한 조건이 없는 경우와 비교하면 각각 0.58, 95%CI=(0.43-0.79), P-값<0.001], [(OR)=0.68, 95%CI=(0.58-0.80), P-값 < 0.001]입니다._x000D_ 당뇨병과 고혈압이 있는 참가자의 경우 암 검진율이 감소한 것으로 나타났습니다. 당뇨병, 고혈압 등 만성질환이 있는 참가자의 암 검진율 감소에 대한 메커니즘을 조사하기 위해서는 많은 연구가 필요하지만, 이전 연구에서는 이러한 낮은 검진율이 만성질환 환자의 의료 서비스에 대한 꺼리는 태도에 기인할 수 있다고 강조했습니다. 그들은 선별 서비스의 비교 이점을 과소평가합니다. 본 연구는 한국의 암 검진 프로그램이 암 검진 절차의 중단을 줄이고, 만성질환자의 암 검진율을 향상시켜 향후 합병증을 줄이고 사망률을 높이기 위한 추가 경로를 고려해야 함을 강조했습니다._x000D_ 키워드: 당뇨병, 고혈압, 암, 검진, 한국
학위논문(박사)--의학과,2024. 2
Keywords: Diabetes; hypertension; cancer; screening; Korea